Frequency of New Onset Salmonella Positive Cases in Children who Received Typhoid Conjugate Vaccine versus Unvaccinated Children - Zaheer, Ramsha; Waseem, Rizwan (Indus Journal of Bioscience Research, 2025)
Objective: The objective of the study is to find the frequency of Typhoid Conjugate vaccination in children of age 1-15 years. Study Design: It was a descriptive cross-sectional study. Place and Duration of Study: Department of Pediatrics, Ghurki Teaching Trust Hospital, Lahore for the period w.e.f July 2023 to January 2024. Material and Methods: Two hundred (200) children, who fulfilled the selection criteria, were recruited for study from OPD of Department of Pediatrics, Ghurki Trust Teaching Hospital, Lahore. The written consent was taken from the Parents. Demographics were noted. Then, all the children were managed as per standard protocol. History from children was taken about TCV vaccination. Blood sample were taken in a 3 cc disposable syringe and was sent to pathology department to detect the presence of salmonella typhi. Reports were assessed and if salmonella typhi detected, then it was recorded. Data was analyzed using SPSS version 20.0.  Results: The study cohort had a mean age of 8.60±4.46 years, with 52% male participants. The mean weight was 25.61±9.33 kg and height 122.00±24.70 cm. Symptoms lasted 11.35±3.40 days. Typhoid conjugate vaccine (TCV) was administered to 56.5% of children, with 18% diagnosed with typhoid. TCV recipients had a significantly lower infection rate (12.4%) compared to non-recipients (25.3%; p=0.019) where p reflects the time internal between vaccination (TCV) and this infection.  Differences across age, gender, weight, height, symptoms, and presentation reasons did not achieve statistical significance due to small sample size. Conclusion: In conclusion, our study underscores a discernible and significant link between the administration of the Typhoid Conjugate Vaccine (TCV) and a lowered incidence of typhoid infections.